Region-specific modulations in oscillatory alpha activity serve to facilitate processing in the visual and auditory modalities - Mazaheri, Ali; van Schouwenburg, Martine R.; Dimitrijevic, Andrew; Denys, Damiaan; Cools, Roshan; Jensen, Ole (NeuroImage (Orlando, Fla.), 2014)
There have been a number of studies suggesting that oscillatory alpha activity (~10Hz) plays a pivotal role in attention by gating information flow to relevant sensory regions. The vast majority of these studies have looked at shifts of attention in the spatial domain and only in a single modality (often visual or sensorimotor). In the current magnetoencephalography (MEG) study, we investigated the role of alpha activity in the suppression of a distracting modality stream. We used a cross-modal attention task where visual cues indicated whether participants had to judge a visual orientation or discriminate the auditory pitch of an upcoming target. The visual and auditory targets were presented either simultaneously or alone, allowing us to behaviorally gauge the “cost” of having a distractor present in each modality. We found that the preparation for visual discrimination (relative to pitch discrimination) resulted in a decrease of alpha power (9–11Hz) in the early visual cortex, with a concomitant increase in alpha/beta power (14–16Hz) in the supramarginal gyrus, a region suggested to play a vital role in short-term storage of pitch information (Gaab et al., 2003). On a trial-by-trial basis, alpha power over the visual areas was significantly correlated with increased visual discrimination times, whereas alpha power over the precuneus and right superior temporal gyrus was correlated with increased auditory discrimination times. However, these correlations were only significant when the targets were paired with distractors. Our work adds to increasing evidence that the top–down (i.e. attentional) modulation of alpha activity is a mechanism by which stimulus processing can be gated within the cortex. Here, we find that this phenomenon is not restricted to the domain of spatial attention and can be generalized to other sensory modalities than vision. •We investigated the role of alpha modulation outside the spatial attention domain.•Cues instructed participants to perform either visual or auditory discrimination.•Visual discrimination cues modulated alpha power in visual cortex.•Auditory discrimination cues modulated alpha power over the supramarginal gyrus.•We find that the role of alpha in attention is not restricted to the spatial domain.